Ilai Rowner. The Event: Literature and Theory. U of Nebraska P, 2015. - Dane Stalcup (Studies in 20th & 21st Century Literature, 2019)
Review of Ilai Rowner. The Event: Literature and Theory. U of Nebraska P, 2015. xv + 311 pp.
Keywords: review; theory; event